The potential and reality of the Living Lab model of ICT for Development (ICT4D) in the rural development context : the case of Siyakhula Living Lab, Dwesa, Eastern Cape, South Africa - Mosuoe, Teboho Priscilla (Rhodes University, Faculty of Humanities, Department of Sociology, 2014)
This thesis explores the contribution of Information and Communication Technology (ICT) in rural development processes. Within the framework of social capital theory, and in the context of the information society, the study examines how the collaborative and innovative model of ICT for Development (ICT4D) can enhance social networks and information channels in rural communities, thereby enabling the active participation of rural community members in their own development processes. The study examines networks and information channels both within the rural communities under investigation and between these communities and other sectors in the society. The thesis studies the case of the Siyakhula Living Lab (SLL), an ICT4D initiative in the Mbashe Municipality of the Eastern Cape Province of South Africa. During the investigation, four types of networks were identified: local organisations, social institutions, collective community projects and social ties. It was found that the Living Lab has so far influenced the creation of new forms of networks through the common spaces (computer labs) which have been made available by the Living Lab. The study further showed that the use of computers has enabled other community members to partake in the wider community of online/virtual social networks, allowing them to communicate and share information with those outside their own communities. The study also showed that the Living Lab has enabled the networking of these communities with other sectors such as academia. It was, however, found that so far the existence of the Living Lab has not influenced the already existing local networks in these communities. Also, the study showed that the relationship between these rural communities and their government and industry partners as stakeholders in the Living Lab is currently ineffective. Nevertheless, this situation has a potential to change in the future as there are ICT applications which have been developed through collaboration with rural community members, which will assist in enhancing communication between these rural communities and other stakeholders. The study finally revealed that social networks do contribute to the functioning of communities by providing both monetary and social support to community members, even though, in effect, the monetary benefits are somewhat limited by a number of factors. It is revealed that the engagement of ICT could go a long way in improving social and economic activities, governance and service delivery, as well as education in these communities.
Keywords: Siyakhula Living Lab; Information technology -- South Africa -- Dwesa-Cwebe; Communication in economic development -- South Africa -- Dwesa-Cwebe; Rural development projects -- South Africa -- Dwesa-Cwebe; Rural development -- Economic aspects -- South Africa -- Dwesa-Cwebe; Rural development -- South Africa -- Dwesa-Cwebe -- Sociological aspects; Rural development projects -- Evaluation; Social networks -- South Africa -- Dwesa-Cwebe